Sosialisasi Pemanfaatan Lahan di Terminal Sangi-Sangi Kab. Konawe Selatan dalam Mendorong Perputaran Ekonomi - Syaiful; LM Anzar Ahlan; Rina Sutriana; Firmansyah; Maudhy Satyadharma; Hado; Galih Adi Sulistyo; Ahiula; Muh. Faza Al Maliki (Universitas Cenderawasih, 2025)
Terminal land utilization is a crucial aspect in improving the effectiveness of transportation services, developing the local economy, and optimizing regional spatial planning. However, various issues such as inappropriate land use, lack of understanding among the public and business actors, and weak coordination between stakeholders remain challenges in terminal management. This community service activity aims to provide outreach regarding the importance of appropriate and sustainable terminal land utilization. The methods used included outreach, focus group discussions, and participant understanding assessments. The outreach activity lasted one day (Saturday, November 8, 2025), targeting the community around the Sangi-Sangi Type B Terminal in South Konawe Regency. The results showed a significant increase in understanding of terminal functions, land zoning regulations, legal business opportunities, and the positive impact of terminal development on the regional economy. This activity is expected to be the first step in strengthening terminal governance to be more efficient, orderly, and economically valuable for South Konawe Regency.